Grid integration of PMSG based wind energy conversion with battery storage system - Venkatachalam K M,; V. Saravanan (International Journal of Applied Power Engineering (IJAPE), 2021)
In this paper, the design and implementation of a permanent magnet synchronous generator (PMSG) based wind energy conversion system and battery bank storages are connected to utility grid. It has phase locked loop (PLL) control strategy as it provides for control single-phase grid connected inverter with constant dc-link voltage. The dc-link is interfaced to a permanent magnet synchronous generator through diode bridge rectifier (DBR) with dc-dc boost converter, battery bank and single phase voltage source inverter (VSI). The dc-link voltage is maintained constant value of 48 V by controlling dc-dc converter with help of perturb and observe (P&O) algorithm based maximum power point tracker (MPPT). The VSI output voltage and frequency values are controlled based on grid parameters using PI controller and sinusoidal pulse width modulation (SPWM) technique. In this grid connected system is simulated and performances are analyzed through MATLAB software. The prototype experimental results are verified through 1 kW PMSG, 48 V battery bank with single phase grid connected system.